Anti-apoptotic and moderate anti-inflammatory effects of berberine in sulfur mustard exposed keratinocytes. (1st September 2018) - Lang, Simon; Popp, Tanja; Kriegs, Christian Silvester; Schmidt, Annette; Balszuweit, Frank; Menacher, Georg; Kehe, Kai; Thiermann, Horst; Gudermann, Thomas; Steinritz, Dirk
Highlights: Sulfur mustard (SM) toxicity was assessed by a mono- and co-culture in vitro model. Effects of berberine (BER) on SM-induced cell damage was analyzed. Viability, apoptosis, necrosis, IL-6 and IL-8 were chosen as surrogate endpoints. BER reduced SM-caused apoptosis, and IL-6 and IL-8 secretion in both models. Necrosis was not significantly changed by BER treatment. Abstract: Skin affections after sulfur mustard (SM) exposure include erythema, blister formation and severe inflammation. An antidote or specific therapy does not exist. Anti-inflammatory compounds as well as substances counteracting SM-induced cell death are under investigation. In this study, we investigated the benzylisoquinoline alkaloide berberine (BER), a metabolite in plants like berberis vulgaris, which is used as herbal pharmaceutical in Asian countries, against SM toxicity using a well-established in vitro approach. Keratinocyte (HaCaT) mono-cultures (MoC) or HaCaT/THP-1 co-cultures (CoC) were challenged with 100, 200 or 300 mM SM for 1 h. Post-exposure, both MoC and CoC were treated with 10, 30 or 50 μM BER for 24 h. At that time, supernatants were collected and analyzed both for interleukine (IL) 6 and 8 levels and for content of adenylate-kinase (AK) as surrogate marker for cell necrosis. Cells were lysed and nucleosome formation as marker for late apoptosis was assessed. In parallel, AK in cells was determined for normalization purposes. BER treatment did not influence necrosis, but significantly decreased apoptosis. Anti-inflammatory effects were moderate, but also significant, primarily in CoC. Overall, BER has protective effects against SM toxicity in vitro . Whether this holds true should be evaluated in future in vivo studies.